2018
DOI: 10.1002/pon.4611
|View full text |Cite
|
Sign up to set email alerts
|

Interventions developed with the Intervention Mapping protocol in the field of cancer: A systematic review

Abstract: Culturally relevant interventions were developed with the IM protocol that were effective to increase cancer screening and reduce social disparities, particularly when they were developed through a participative approach and integrated the environment. Stakeholders' involvement and the role of the environment were heterogeneously integrated in the interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 79 publications
0
30
1
4
Order By: Relevance
“…However, many studies are less likely to completely explore the critical determinants of program effectiveness such as factors influencing behavior of breast cancer survivors regarding behavioral change model application [31]. In order to develop such programs for breast cancer survivors it is suggested that the researcher makes use of Intervention Mapping (IM) [32,33]. IM is a framework which assists researchers to develop intervention programs based on the best theories for certain populations, as well as a suitable evaluation framework [32].…”
Section: Theories and Other Approaches Related To Behavioral Change Fmentioning
confidence: 99%
See 2 more Smart Citations
“…However, many studies are less likely to completely explore the critical determinants of program effectiveness such as factors influencing behavior of breast cancer survivors regarding behavioral change model application [31]. In order to develop such programs for breast cancer survivors it is suggested that the researcher makes use of Intervention Mapping (IM) [32,33]. IM is a framework which assists researchers to develop intervention programs based on the best theories for certain populations, as well as a suitable evaluation framework [32].…”
Section: Theories and Other Approaches Related To Behavioral Change Fmentioning
confidence: 99%
“…In order to develop such programs for breast cancer survivors it is suggested that the researcher makes use of Intervention Mapping (IM) [32,33]. IM is a framework which assists researchers to develop intervention programs based on the best theories for certain populations, as well as a suitable evaluation framework [32].…”
Section: Theories and Other Approaches Related To Behavioral Change Fmentioning
confidence: 99%
See 1 more Smart Citation
“…IM is one of the most comprehensive systematic approaches for the development of theory and evidence-based behavior change interventions, and it is a framework that is characterized by a participative approach involving the relevant stakeholders [29,30]. This framework has been used regularly in the development and implementation of both cancer-related [31] and work-related interventions [32][33][34][35]. The IM framework consists of six consecutive steps, with the results of each step guiding the subsequent one: step 1, needs assessment; step 2, formulating objectives using a logic model of change; step 3, selecting theories and practical strategies; step 4, developing the intervention; step 5, planning for program adoption and implementation; and step 6, planning for evaluation [30].…”
Section: Methodsmentioning
confidence: 99%
“…HB's development was inspired by the intervention mapping protocol and stresses the stages of needs assessment; the intervention's expected results; selection and description of methods based on theory and their applications supported by evidence for their success; conception and implementation of the intervention carried out; and results evaluation (Bartholomew, Parcel, Kok, Gottlieb, & Fernández, 2011;Murta & Santos, 2015;Schaafsma, Stoffelen, Kok, & Curfs, 2013). Intervention mapping (IM) is a systematic approach to plan interventions used worldwide (De Lepeleere, Verloigne, Brown, Cardon, & De Bourdeaudhuij, 2018;Lamort-Bouché et al, 2018), which holds that health interventions based on theory and their applications tend to be more successful (Bartholomew et al, 2011). The intervention aimed to establish change goals and objectives that would promote the adoption of HMP elements, such as a framework to broaden and strengthen mental health programs that assist people having NOSC experiences.…”
Section: Introductionmentioning
confidence: 99%